Genetic variability of influenza virus and vaccine effectiveness - Guiomar, Raquel (2015)
Euroeva is the portuguese component of the multicentric study I-MOVE (influenza monitoring vaccine effectiveness in Europe) that aims to estimate influenza vaccine effectiveness in Europe. As an higher vaccine effectiveness is expected when circulating viruses are similar to the vaccine strains, this study aims to describe circulating strains and amino acid substitutions in antigenic sites in order to better understand VE changes along seasons.